Analysis Of Financial Performance on The Dividend Policy of Mining Companies Listed On The IDX in 2017-2021 - Nasution, Anggi Mulianur; Pramono, Cahyo (Universitas Negeri Medan, 2023)
The rapid development of the mining sector that has occurred in Indonesia in recent years attract investors to invest in this sector. financial reports that describing the financial condition of a company is information that can be used to help investors and other capital market participants to make decisions as well assess the condition or financial performance of a company. One of the analytical tools used by investors to assess the company's financial performance mining sector is to use financial ratio analysis (financial ratio analysis), both liquidity ratios, solvency ratios and profitability ratios obtained from Company Financial Statements. This research is a descriptive study, with a purposive sampling technique sampling and using secondary data in the form of annual financial reports over a period of time 5 (five) years from 2017-2021 from 3 (three) large companies in the mining sector listing on the Indonesia Stock Exchange, namely PT. Adaro Energy Tbk, PT. Indika Energy Tbk, and PT. Dian Swastika Sentosa Tbk. The research results show that overall during the last 5 years the sub-sector Mining has experienced quite significant growth marked by an increase the average financial ratio of the mining industry. During the research period PT. Adaro Energy Tbk and PT. Dian Swastika Sentosa Tbk has a value of liquidity ratios, solvency ratios and good profitability ratios while PT. Indika Energy Tbk. have a high liquidity ratio good, suffered a loss in 2017-2019 but has made a profit in 2021 and The company is still in an insolvent position. The research results are expected to help investors in comparison with other companies from various types of various industries.